Preparation and Characterization of Ce-Zr/Al-MCM-41 Bimetallic Catalyst for Transesterification of Jatropha Oil to Biodiesel - Jibril, Z.I. (Institute of Physics Publishing, 2018)
A series of bimetallic Ce-Zr heterogeneous catalysts supported on Al-MCM-41 aluminosilicate with cerium and zirconium loading ranging from 2.5 to 7.5 wt, were prepared by co-impregnation method. The characterization of the catalysts obtained by various analytical methods; XRD, N2 adsorption-desorption, FESEM, EDX and TPD NH3. The result shows that metals were well incorporated in the framework of the support, catalysts retained the mesoporous character and stability of structure after impregnation. The catalysts were active in one step transesterification of non-edible jatropha oil to produce fatty acid methyl esters (FAME) with methanol to oil ratio 6:1 at 90C, after 4 h reaction time. The FAME yield was found to have the maximum activity, higher than 80 with catalyst 5 wt Ce and 5 wt Zr loadings supported by Al-MCM-41 with catalyst loading 5 wt. The catalyst was recovered by simple filtration. Â© Published under licence by IOP Publishing Ltd.